The method of combination of electroconvulsive therapy and postictally hypnotherapy in the treatment of patients with therapeutically resistant depression - Chugunov, V. V.; Kurilo, V. A.; Danilevska, N. V.; Grigoryan, A. Z.; Чугунов, В. В.; Курило, В. А.; Данилевская, Н. В.; Григорян, А. З.; Чугунов, Вадим Віталійович; Курило, Віталій Олексійович; Данілевська, Наталя Володимирівна; Григорян, Артур Зоренович (My University, 2016)
The description of the new method of treatment of therapeutically resistant depression by electroconvulsive therapy in combination with postictally hypnotherapy id given. Clinical and psychometric evaluation of the effectiveness of the new technique has been conducted. The results obtained show high efficacy of the method under description. Приведено описание новой методики лечения терапевтически резистентной депрессии – электросудорожной терапии в комбинации с постиктальной гипнотерапией. Проведена клиническая и психодиагностическая оценка эффективности разработанной методики.
Комбинация электросудорожной терапии и постиктальной гипнотерапии в лечении пациентов с терапевтически резистентной депрессией
Keywords: electroconvulsive therapy; depression; postictally hypnotherapy; электросудорожная терапия; депрессия; постиктальное внушение